Enhancing Student Self-Disclosure through the Deep Talk Critical Method: A Case Study of Islamic Religious Education - Nabilah Khalda; Muslimah Muslimah; Surawan Surawan (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze how the Deep Talk Critical method is applied by Islamic Religious Education (PAI) teachers to enhance student self-disclosure and the impacts of this method on learning effectiveness. Methodology: This qualitative field research employed triangulation of data sources, including interviews, observation, surveys, and documentation. The Miles and Huberman analysis model comprising data reduction, data display, and conclusion drawing was used. The study also defined four self-disclosure indicators: openness, empathy, support, and equality, based on interpersonal communication theories. Main Findings: Findings indicate the Deep Talk Critical method is highly effective (85.72%) in fostering student self-disclosure. Specific indicators showed high performance: empathy (90.41%), equality (88.63%), support (84.87%), and openness (78.97%). Novelty/Originality of this study: This study contributes to PAI communication strategy literature by formalizing Deep Talk Critical as a practical pedagogical model for strengthening self-disclosure and emotional intelligence among students.